ESTUDO DE MATERIAIS HETEROESTRUTURADOS FUNCIONAIS À BASE DE HIDRÓXIDOS DUPLOS LAMELARES SUPORTADOS EM SILICATO LAMELAR. - FERNANDES JÚNIOR, Antonio de Jesus dos Santos (2017)
In this work,a nevel material heterostructured based on the assembly of double layered double hydroxide (LDH) suported in magadiite, was synthesized. For this purpose, layered double hydroxides of MgAl and ZnAl,both in the proportion 2:1 was synthesized by the method of coprecipitation in situ in the presence of magadiite.Diverse physicochemical techniques (DRX,FTIR,DTA,ICP-OES,MEV E TEM ) were employed to caractherize the materials syntehesized with the aim of verifying the existence of interactions in the interface of both components. Results gotten by DRX show plans of reflection typical of magadiite,confirming the formation o HDL in the surface of silicate. Nanocrystalline interactions among the groups of hydroxyl of each component. Metalic Oxide nanoparticles were supported in magadiite employing the thermic decomposition (calcination) of the component HDL present in the hetero-structure MAG/HDL,with the aim of getting catalyst formed by metalic oxides highly dispersed supported in magadiite. Calcined materials and non-calcined were evaluated as photocatalysts, using blue dye of methylene as a standard molecule. Photocatalytic analyses were made with “heterostructure” MAG/HDL and MAG/ODL showed a catalytic activity improved in order to degradate the dye,,where the concentration decreased considerablly in a short interlude of exposition to irradiation of uv light in camparison to the photlysis test.These results were gotten probably thanks to the resulting synergistic effect of textured properties interesting,charactheristics of synthesized heterostructured ,turning them in photocatalytic promising in the degradation of organic compounds.